Randomised phase II trial of olaparib, chemotherapy or olaparib and cediranib in patients with platinum-resistant ovarian cancer (OCTOVA): a study protocol. Issue 1 (15th January 2021) - Mansouri, Anita; McGregor, Naomi; Dunn, Rachel; Dobbie, Sam; Holmes, Jane; Collins, Linda; Nicum, Shibani
Abstract : Introduction: Patients relapsing within 12 months of platinum-based chemotherapy usually have a poorer response to subsequent treatments. To date, extensive research into the mechanism of resistance to platinum agents in the treatment of ovarian cancer has not resulted in improved responses or longer survival. Further experimental work and clinical trials with novel agents are therefore justified to address this unmet need. Patients with ovarian, fallopian tube or primary peritoneal cancer that has relapsed within 12 months of platinum-based chemotherapy will be randomised with stratification for BReast CAncer gene (BRCA) status, prior poly (ADP-ribose) polymerase (PARP) exposure and prior antiangiogenic therapy into weekly paclitaxel (chemotherapy), olaparib or the combination of cediranib and olaparib. They will be followed until disease progression or unacceptable toxicity develops. Our trial design permits two investigations. We will compare the efficacy and tolerability of single-agent olaparib with weekly paclitaxel. We will also compare the efficacy and tolerability of olaparib with the combination of olaparib and cediranib. The required sample size of 138 participants (46 per arm) was calculated using a 20% one-sided type I error, 80% power and 15% dropout rate. Recruitment will last 34 months with a follow-up of 18 months. Methods and analysis: Ethics and dissemination: This study will be conducted under a UK Medicines and Healthcare Products Regulatory Agency Clinical Trials Authorisation. Approval to conduct the study was obtained from the responsible authority before beginning the study. The sponsor will retain ownership of all data arising from the trial. We aim to publish this research in a specialist peer-reviewed scientific journal on study completion. EudraCT number: 2016-000559-28, ethics reference number: 16/LO/2150. Trial registration number: ISRCTN: ISRCTN14784018, clinicaltrials.gov: NCT03117933; Pre-results .